Impact of sarcopenia on functional and cognitive recovery in Caucasian post-stroke patients following rehabilitation - Guerrini, Alessandro; Siotto, Mariacristina; Fasano, Alessio; Cocco, Carola; Germanotta, Marco; Cipollini, Valeria; Cortellini, Laura; Pavan, Arianna; Lattanzi, Stefania; Insalaco, Sabina; Antonacci, Erika; Ruco, Elisabetta; et al. (Frontiers in Nutrition, 2025)
Background & aimsSarcopenia, a progressive and generalized skeletal muscle disorder, significantly hinders post-stroke recovery. Existing research has focused exclusively on Asian populations, leaving effects in Caucasian cohorts largely unexplored. This study aims to evaluate the impact of sarcopenia, as defined by the European Working Group on Sarcopenia in Older People (EWGSOP2) criteria, on functional and cognitive recovery in subacute post-stroke patients undergoing a rehabilitation program.MethodsEighty seven subacute post-stroke patients (71 [61–78] years; 42 women) were evaluated at admission (T0) and after 6 weeks of rehabilitation (T1). At T0, demographic, clinical, and nutritional data were collected, and sarcopenia was diagnosed. Functional and cognitive outcomes—including the modified Barthel Index (mBI), Fugl-Meyer Assessment for Upper Extremity (FMA-UE), Motricity Index for upper and lower limbs (MI-UE, MI-LE), Functional Ambulation Category (FAC), and Montreal Cognitive Assessment (MoCA)—were evaluated at both T0 and T1. Functional and cognitive recovery (ΔmBI, ΔFMA-UE, ΔMI-UE, ΔMI-LE, and ΔMoCA) were also assessed. Intra-group (T0 vs. T1) and inter-group comparisons (sarcopenic vs. nonsarcopenic patients) were then evaluated, and a Propensity Score Matching (PSM) analysis was used to adjust for baseline confounding factors.ResultsSarcopenic patients (n = 24; 14 women) showed poorer nutritional status and lower scores in all functional and cognitive measurements at T0 compared to their non-sarcopenic counterparts. Both groups improved significantly at T1 in mBI, FMA-UE, MI-UE, MI-LE, and FAC. However, even after PSM analysis, the sarcopenic patients exhibited lower FAC (0 [0–1] vs. 3 [1–3], p = 0.010) and lower mBI (40 [27–57] vs. 57 [47–72], p = 0.044) scores at T1, along with a reduced ΔmBI (6 [0–14] vs. 15 [8–21], p = 0.014).ConclusionOur findings emphasize that sarcopenia negatively affects post-stroke recovery of independence and ambulation, highlighting the importance of early identification and targeted interventions in rehabilitation.